Populasi Dan Tingkat Serangan Kumbang Tanduk (Oryctes Rhinoceros L.) Pada Pertanaman Kelapa Sawit Di PT. Cakra Alam Sejati, Provinsi Riau - Adam Jorli Wong; Hidrayani; Hasmiandy Hamid; Zahlul Ikhsan; Aulia Oktavia (Jurusan Budidaya Perkebunan, 2022)
The increasing area of oil palm plantations (Elaeis guineensis Jacquin) in Indonesia every year creates opportunities for pest that can harm oil palm plantations to develop, one of which is the coconut palm rhinoceros beetle (Oryctes rhinocheros Linnaeus). This research aims to determine the coconut palm rhinoceros beetle population, the percentage of plants attacked, and the intensity of the attack on the planting area Kebun-24 palm plantations of PT. CAS (Cakra Alam Sejati). In this research used a survey method on oil palm plantations Kebun-24. Determination of sample blocks was carried out by purposive sampling and plant samples were selected randomly. The location of the research was carried out in Pelalawan Regency, namely in the Kebun-24 plantation of PT. CAS, Riau Province. The results of the research, the highest population was TBM block with an average of 11.27 coconut palm rhinoceros beetle individuals. The highest coconut palm rhinoceros beetle population was in block 4c (1 year) with 86 imago individuals and 126 larvae individuals, while the lowest population was in block 11a (8 years) with 14 imago individuals and 68 larvae individuals. The highest percentage of affected plants was TM block with an average of 98.67%. The highest attack intensity of coconut palm rhinoceros beetle was TM block with an average of 37.07%. The percentage of affected plants and the highest attack intensity were in block 7b (6 years) with 100% percentage of affected plants and 37.60% attack intensity, while the lowest was block 14b (2 years) with 72.00% percentage of affected plants and 32, 00% attack intensity